2016
DOI: 10.1155/2016/1084670
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of the Antimicrobial Agent Beauvericin from the EndophyticFusarium oxysporum5-19 with NMR and ESI-MS/MS

Abstract: Endophytic microbe has been proved to be one of rich sources of bioactive natural products with potential application for new drug and pesticide discovery. One cyclodepsipeptide, beauvericin, was firstly isolated from the fermentation broth of Fusarium oxysporum 5-19 endophytic on Edgeworthia chrysantha Linn. Its chemical structure was unambiguously identified by a combination of spectroscopic methods, such as HRESI-MS and 1H and 13C NMR. ESI-MS/MS was successfully used to elucidate the splitting decomposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…As described by Xu et al ( 2010 ), the median effective inhibitory concentration values of BEA against 6 test bacteria ( B. subtilis, S. haemolyticus, P. lachrymans, A. tumefaciens, E. coli , and X. vesicatoria ) were between 18.4 and 70.7 μg/mL. In another study (Zhang et al, 2016 ), BEA showed an inhibitory effect on three human pathogenic microbes, C. albicans, E. coli , and S. aureus . In particular, BEA exhibited the strongest antimicrobial activity against S. aureus with MIC values of 3.91 μM.…”
Section: Bioactivitymentioning
confidence: 79%
“…As described by Xu et al ( 2010 ), the median effective inhibitory concentration values of BEA against 6 test bacteria ( B. subtilis, S. haemolyticus, P. lachrymans, A. tumefaciens, E. coli , and X. vesicatoria ) were between 18.4 and 70.7 μg/mL. In another study (Zhang et al, 2016 ), BEA showed an inhibitory effect on three human pathogenic microbes, C. albicans, E. coli , and S. aureus . In particular, BEA exhibited the strongest antimicrobial activity against S. aureus with MIC values of 3.91 μM.…”
Section: Bioactivitymentioning
confidence: 79%
“…Bioassy-guided fractionation of the fermentation crude of strain R1 lead to isolation of two compounds 1 and 2 using HPLC method. By a combination of their 1D NMR and ESI-MS data as well as comparison with literature, compounds 1 and 2 were respectively characterized as dibutyl phthalate (Wu et al, 2017), beauvericin (Zhang et al, 2016) (Figure 4). And the yield of compound 1 was about 1.17 mg/L while that of compound 2 was 2.5 mg/L.…”
Section: Structure Elucidation Of Secondary Metabolites From Strain R1mentioning
confidence: 92%
“…Antimicrobial activity was assessed by the microbroth dilution method in 96-well culture plates according the procedure developed by our lab (Zhang et al, 2016). All test compounds were dissolved in DMSO (100 μg•mL -1 ).…”
Section: Antimicrobial Assay Of Compounds 1 Andmentioning
confidence: 99%
See 2 more Smart Citations